Asesmen Produktivitas Ternak dan Kesesuaian Potensi Tanaman Pertanian Sebagai Hijauan Pakan: Sebuah Potret Kawasan Agro-Ekologi Dataran Rendah Selatan Merauke, Papua - Hieronymus Yohanes; Yafed Muyan; Sientje Rumetor; Jhon Arnold Palulungan; Alnita Baaka; Dwi Nurhayati; Maria Arim; Desni Saragih; Aisyah Bauw; Yafed Syufi; Maya Novi; Jasmal Syamsu; Deny Anjelus Iyai; Elfira Kariane Suawa; Siti Halimatus Saadiyah; Hans Mamboai; Stepanus Pakage; Makarius Bajari (Institut Pertanian Bogor, 2022)
The study aimed to descriptively capture livestock production and food waste and the suitability of border farms in the lowland Merauke region. Data were analyzed on livestock population structure (individual/ST), food crop waste production (dry weight, DW), capacity, and location quotient (LQ), and SWOT. Food crop waste production is 350 thousand tons of DW and so far only provided for ruminant cattle about 11%. Food crop straw waste is still dominated by rice straw (97%), followed by corn waste (2%), sweet potatoes, and peanuts. The capacity to increase the cattle population is close to 315 thousand ST. The LQ value of both livestock and food crops in Merauke is still in the range of 0 -<1 and is still a prospective sector to be optimized. The results of SWOT analysis conclude that the S-O strategy is the intensification and expansion of livestock commodities. Keywords: livestock population structure, location quotient, KPPTR, crop residues, Merauke